EDUKASI ASI EKSKLUSIF SEBAGAI UPAYA PENCEGAHAN STUNTING DI WILAYAH KERJA PUSKESMAS JABIREN KABUPATEN PULANG PISAU - Normila, Normila; Maulia, Resna; Fauziah, Lena Zahra (Universitas Mataram, 2024)
Stunting among toddlers poses a serious public health issue in Indonesia. The SSGI data of 2022 indicates that the prevalence of stunting remains high, particularly in certain regions. Central Kalimantan stands out as one of the areas where the rates exceed the national average. The causes of stunting are multifaceted, involving factors such as malnutrition, unhealthy eating patterns, and limited access to appropriate healthcare services and nutritional information. Among these factors, the practice of exclusive breastfeeding (EBF) plays a crucial role in stunting prevention. The aim of this research is to enhance understanding and practice of Exclusive Breastfeeding to mitigate the risk of stunting. The method employed in community engagement activities is conducting informative sessions utilizing flip charts. There were 22 participants, including pregnant women, breastfeeding mothers, and health cadres. Evaluation was conducted through pre-test and post-test assessments. The results were then statistically analyzed using the McNemar test. The findings reveal a significant difference in knowledge before and after the education intervention, with a p-value of 0.001 (<0.05). Prior to the intervention, 40% of participants demonstrated good knowledge, while post-intervention, 100% were categorized as having good knowledge. Utilizing flip charts for education effectively enhanced participants' understanding of exclusive breastfeeding.